High Sensitive Enzyme Based Glucose Sensor Using Lead Sulfide Nanocrystals - Doanh, Sai Cong; Quynh, Luu Manh (VNU Journal of Science: Mathematics - Physics; Vol 31 No 2, 2015)
In recent years, glucose oxidase (GO x ) based sugar level detecting techniques have been intensively developed. In order to improve the diagnosis and desease treatment in low- and middle-income countries, the low cost, easily processing, but still high sensitive sensing systems/equipments play a very important rules in biomedicine and life science. In this work, lead sulfide (PbS) nanocolloids were used as electron receptor. The results showed that the sensitivity of the glucose sensor reached 546.2 μA cm -2 mM -1 . It is note that, some early works on GO x based glucose sensor only reached sensitivity less than 100 μA cm -2 mM -1 . Keywords: Lead sulfide nanoparticles, glucose sensor, glucose oxidase.